Node-Place Model Analysis on Attached Transit Oriented Development (TOD) Areas : The Case of Wates Train and Bus Station Area - Muhammad Yusuf Alfyan; Dyah Titisari Widyastuti (Department of Architecture and Planning, Faculty of Engineering, Universitas Gadjah Mada, 2022)
Wates Train Station (Wates train station) and Wates Bus Station (Wates bus station) are two transportation nodes located in the Wates District moreover provide a wider area in the scale of the Kulon Progo Regency. These two transport nodes are near to each other and intersect within the radius of the TOD area. The presence of the Yogyakarta International Airport in Temon District was projected to increase the transportation intensity on Wates train station yet Wates bus station as the nodes of the current public transport service. This study was aimed to measure the Node - Place (N - P) index on both TOD areas. The Bertolini’s N - P model is a commonly used method on the measurement of TOD performance in terms of the transportation intensity towards land use (activity) intensity. The identifications were based on the TOD theory and the N - P indicators. Measurements were conducted through a weighted multi - criteria analysis. The analysis resulted in the same type of node - place index on both TOD areas, the “unbalanced node”. An unbalanced node indicates poor land use development regards a high transportation capability. Wates train station area has the index of node 0,72 and place 0,25 while the Wates bus station has the index of node 0,64 and place 0,16.